Exploring Appropriate Song Rhythms for Effective Language Learning in the Madrasah Context: Students’ Perspectives - Rokhim, Abdul; Dzulfikri, Dzulfikri (Abjadia : International Journal of Education, 2025)
This study investigates identifying the most appropriate song rhythms to support ideal English language learning in the madrasah context, as viewed from students’ perspectives. A descriptive qualitative approach was employed, involving four students from MTs NU Pakis as participants. Data were collected through classroom observations, questionnaires, and interviews, with data validity ensured through triangulation. The findings indicate that songs with slow to moderate tempo are preferred and perceived as more effective in facilitating listening comprehension, speaking skill, and boosting motivation in language learning. Students reported that such rhythm made it easier to grasp meaning, imitate pronunciation, and reduce anxiety during English lessons. Songs like “I have a dream” and “You raise me up” were found to create a motivating and supportive learning environment. Therefore, rhythm selection plays a significant role in enhancing language acquisition in madrasah-based EFL instruction. This study offers practical insights for EFL practitioners in selecting effective musical aids, emphasizing the critical link between musical rhythm and pedagogical outcomes in religious educational settings.